The Influence of Organizational Culture, Work Environment and Work Motivation on Nurses Performance with Job Satisfaction as a Mediation Variable In Public Health Center XYZ - Afianto, Dennise; Surya Wuisan, Dewi Sri (Pelopor Publikasi Akademika, 2023)
With job satisfaction acting as a mediating variable, the purpose of this study is to evaluate the impact of organizational culture, work environment, and work motivation on nurse performance. This study involved 48 nurses and was carried out in Jakarta. A Likert scale of 1 to 5 was used for 34 questions on the questionnaire, which was distributed as part of the census sampling procedure to collect data. The SEM approach based on PLS was used to analyze the data. The study's findings indicate that the XYZ Community Health Center (Puskesmas) nurses performance is influenced by organizational culture, the work environment, and job satisfaction. This research model is still intriguing and will hopefully add to the performance literature despite a number of limitations